Perancangan Aplikasi Kids Memory Game Berbasis Android - Juliyanto; Octaviandy, Pieter; Pribadi, Octara (STMIK TIME, 2020)
Child growth is the most important moment for a child. Children who are still young must be equipped with useful education so that later it will be useful when the child is growing up. Children's memory is very important to be trained as a child because with the process of memory training it can train the child to be fast in learning something good whether it's a lesson or other general matters. In practice, the learning process to train the child's memory is still done manually, namely by picture books, this is less interesting for the child because children prefer to play while learning. Besides the existing textbooks are quite boring because there are no games or sound effects that attract the child's interest to learn. Therefore, the above problems will be designed an educational game that trains children's memory with the concept of play. The results of this study are in the form of an educational game called Kids Memory Game which is used as a media for children's education and media to train children's memory.